Eksplorasi Airtanah dengan Metode Tahanan Jenis Menggunakan IPI2Win di Kecamatan Dramaga Kabupaten Bogor, Jawa Barat - Ade Ananta Prakusya; Roh Santoso Budi Waspodo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2019)
Fresh water is basic needs for human being. The safest for human consumed is groundwater. Groundwater demand will always increase in accordance with the development of an area. The purposes of this research were to identify the depth of aquifer, to know the effectivity of IPI2Win software, and to analyze potential of groundwater reserves in Dramaga District. Groundwater exploration was conducted using geoelectrical methods. This research had done in Dramaga District since January until June 2018. Data were processed using IPI2Win. Based on 9 points measurement at Dramaga District, the soil layer contained a lot of water. IPI2Win was effective to identify aquifers. Based on GL 1, GL 2, GL 5, and GL 6 measurement points which close to the residence area, the aquifer depth was identified less than 6 m with an error value of <15%. Potential of groundwater reserves for unconfined aquifers was 1048.45 m3/day or 12.13 l/s..Keywords: aquifer, geoelectrical method, groundwater, IPI2Win, resistivity